Perancangan Manajemen Bandwidth Menggunakan PCQ Di SMP Tunas Bangsa - Utari Nurul Fajar Nasution; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Mikrotik has the ability to improve network performance through the RouterOS device. Junior High School named Tunas Bangsa uses a router that has not been configured properly so it has an impact on poor network quality. This is evidenced by the results of the Quality of Service (QOS) measurement from a throughput parameter which is included in the "bad" category based on the TIPHON throughput standard.The solution to improve network performance is design bandwidth management using the Per Connection Queue (PCQ) method. The method is designed for network condition that have many clients where the distribution of bandwidth can be done evenly because PCQ has complexity in determining parameters by grouping based on source and destination traffic.After the configuration done, the QOS calculation is carried out again to prove that the network has gained significant changes. The results show that the throughput has increased based on the TIPHON standard, it is included in the "good" category. This is proof of success in managing bandwidth on the network.Keywords: Mikrotik RouterOS, Network Performance, Per Connection Queue (PCQ).